2012
DOI: 10.1186/1472-6963-12-420
|View full text |Cite
|
Sign up to set email alerts
|

Professional health care use and subjective unmet need for social or emotional problems: a cross-sectional survey of the married and divorced population of Flanders

Abstract: BackgroundThe high mental health care consumption rates of divorced singles may constitute a heavy burden on the public health care system. This raises the question of whether their higher health care use stems from a greater need, or whether there are other factors contributing to these high consumption rates. We examine both health care use and subjective unmet need (perceiving a need for care without seeking it) because of social or emotional problems of the divorced singles, the repartnered divorcees, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 70 publications
(109 reference statements)
2
16
1
1
Order By: Relevance
“…If this hypothesis is correct, it would suggest that people who feel that they have not been helped will more often hesitate to return to their health care provider if they are confronted with problems again. In line with this assumption, a study of Colman and colleagues, employing the same survey data as the current study, has shown that non-frequent health care users more often perceive an unmet need than frequent health care users and non-users (Colman et al, 2012). We thus predict that a lower perception of helpfulness will be associated with less frequent contacts among health care users (hypothesis 2a).…”
Section: Introductionsupporting
confidence: 76%
See 4 more Smart Citations
“…If this hypothesis is correct, it would suggest that people who feel that they have not been helped will more often hesitate to return to their health care provider if they are confronted with problems again. In line with this assumption, a study of Colman and colleagues, employing the same survey data as the current study, has shown that non-frequent health care users more often perceive an unmet need than frequent health care users and non-users (Colman et al, 2012). We thus predict that a lower perception of helpfulness will be associated with less frequent contacts among health care users (hypothesis 2a).…”
Section: Introductionsupporting
confidence: 76%
“…This resulted in a response rate of 43.3% among the divorced and 39.5% among the married, and a sample of 4538 respondents. Descriptive analyses of this sample and the correlates of professional health care use and subjective unmet need can be found elsewhere (Colman et al, 2012).…”
Section: Sample and Populationmentioning
confidence: 99%
See 3 more Smart Citations